Hypotensive Response to Continuous Aerobic and High-Intensity Interval Exercise Matched by Volume in Sedentary Subjects - Boeno,Francesco Pinto (2019)
Abstract Background: Systemic arterial hypertension (SAH) is one of the main risk factors for heart disease. Among the benefits linked to different modalities of physical exercise, post-exercise hypotension (PEH) is a key point for exercise prescription in this condition. Objective: To investigate and compare PEH in response to continuous aerobic exercise (CONT) and high-intensity interval exercise (HIIE), matched by volume, in sedentary individuals. Methods: A randomized cross-over study, composed of sedentary, healthy male subjects submitted to two acute physical exercise protocols matched by volume, HIIE and CONT, on a treadmill. Hemodynamic measures for the evaluation of PEH were performed pre, immediately after exercise and every five minutes thereafter, during one hour of recovery. Two-way ANOVA with repeated measurements was used for comparisons between groups and Bonferroni post hoc test as appropriate. P < 0.05 was considered significant. Results: Both exercise protocols promoted significant PEH, with reductions in systolic blood pressure (SBP) and mean arterial pressure (MAP). HIIE promoted a reduction of SBP and MAP at the 15th minute, whereas the same effect was observed at the 30th following CONT. Conclusion: Both HIIE and CONT, matched by volume, promote PEH of similar magnitude. However, PEH occurs earlier following HIIE, suggesting a better time / effectiveness ratio, and an additional beneficial effect of this modality.